Is microfinance program in Malaysia really effective in helping the poor? - Hamdan, Hamdino; Othman, Pazim @ Fadzim; Wan Hussin, Wan Sabri (World Business Institute, Australia, 2012)
Microfinance1 program is becoming more significant as the main contributor in creating new job opportunities and generating income for increasing social well-being and economic status of the poor and eradicating poverty. Basically, the microfinance program in Malaysia has been administered by various institutions and non-banking government agencies. The most important institutions for this study are Lembaga Zakat Selangor (LZS), Yayasan Basmi Kemiskinan (YBK) Selangor, Amanah Ikhtiar Malaysia (AIM) and Yayasan Tekun Nasional (TEKUN). The focus of this study is to evaluate the effectiveness of YBK Selangor, AIM, TEKUN and LZS microfinance programs in increasing the participants’ income and eradicating poverty by conducting microenterprise businesses through the adoption of entrepreneurial concept. Based on the univariate and multivariate analysis, the results show that AIM is the most effective microfinance program as it enables the poor to increase their income and improve their social well-being. The study also shows that monitoring, fund size, purpose of loan usage and total income before participating in the microfinance program are the main factors which influence the level of income that poor people can generate. In addition, Islamic microfinance program which is based on Syariah and Islamic Finance concept has a very high potential in helping the poor people to expand and diversify their economic activities, increase their income and improve their social well-being.